EKSPLORASI IDENTITAS PROFESIONAL PUSTAKAWAN SEKOLAH DI LAMPUNG DALAM MENGHADAPI TRANSFORMASI DIGITAL: EKSPLORASI IDENTITAS PROFESIONAL PUSTAKAWAN SEKOLAH DI LAMPUNG DALAM MENGHADAPI TRANSFORMASI DIGITAL - Ida Nurhaida; Andi Windah; Anita Sartika Dewi (UPT Perpustakaan Universitas Bengkulu, 2026)
he lack of public understanding of the librarian profession makes this profession considered a profession without clear prospects and only as a bookkeeper. Apart from that, this profession tends to be considered an alternative profession and not a profession choice. In practice, in school libraries, the profession of librarian tends to be given to teachers who have fewer performance points. This condition makes the librarian profession not a priority, especially if this position is held by those who do not have librarian competence. Like professions in general, librarians must also have personality and skill qualifications. Apart from that, Law Number 43 of 2007 about libraries, which also regulates librarians. Internal problem formulation this research, namely: (1) what is the level of competence of librarians in inner Lampung facing the digital era, (2) how librarians explore their professional identity, and (3) what factors are obstacles and supports for librarians to develop/improve their professional identity. The aim of this research is, namely, to explain and analyze the initial competencies of the librarian profession in Lampung and explain and analyze how librarians explore identity professionalism based on the competencies they possess. The benefits of this research are: as input material for related individuals and institutions in development efforts; professional identity of librarians, which will ultimately lead to improvement in professionalism of work; and quality of service attached to it. This research uses quantitative descriptive methods, which are supported by result data observations, interviews, and literature studies, which are analyzed through the data display process, reduction, verification, and triangulation. The results of this research are expected to provide a positive contribution to the development of the self-identity and personal branding of librarians so that the librarian profession becomes the main profession in society. In addition, this research will also contribute to the development of the quality of librarians and their main duties and functions accompanying.